2020
DOI: 10.36740/wlek202001127
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Pregnancy and Its Long-Term Results

Abstract: The aim: The purpose of this study was to assess the long-term outcomes of restoration of reproductive function after surgical and medical treatment of ectopic pregnancy, taking into consideration the patency of the fallopian tubes and the incidence of uterine pregnancy. Materials and methods: A two-stage experimental approach was used to address research objectives. In the first stage, a retrospective analysis of 615 histories of patients with ectopic pregnancy has been performed. In a second stage – we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Since ectopic pregnancy is the most common cause for pregnancy related death in the first trimester, a treating physician even in a primary health care facility will benefit with a basic understanding of its pathophysiology and safe management. [ 18 ] With the increased use of high resolution USG and highly sensitive beta HCG assays more and more patients with EP are being diagnosed in the early stages; therefore, a clearer understanding of the rationale and the selection of patients for conservative management will help the patients especially on a long-term basis, for their future fertility[ 2 ] Management for haemodynamically stable patients with unruptured EP should be individualized and a select group of patients can be safely managed even in a primary health care facility. Of all the predictors for success of treatment that have been studied, the initial beta HCG value still remains of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ectopic pregnancy is the most common cause for pregnancy related death in the first trimester, a treating physician even in a primary health care facility will benefit with a basic understanding of its pathophysiology and safe management. [ 18 ] With the increased use of high resolution USG and highly sensitive beta HCG assays more and more patients with EP are being diagnosed in the early stages; therefore, a clearer understanding of the rationale and the selection of patients for conservative management will help the patients especially on a long-term basis, for their future fertility[ 2 ] Management for haemodynamically stable patients with unruptured EP should be individualized and a select group of patients can be safely managed even in a primary health care facility. Of all the predictors for success of treatment that have been studied, the initial beta HCG value still remains of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical scenario has changed now with EP being diagnosed much earlier with the help of high resolution ultrasonography (USG) and highly sensitive beta HCG assays which have revolutionised the management of unrupturedEP. [ 1 2 ] Different management protocols are currently available but definitive recommendations is yet to be established, especially in developing countries with limited resources. [ 3 ]…”
mentioning
confidence: 99%
“…Therefore, for patients with EP with stable hemodynamics and appropriate indications, MTX treatment should be prioritized to better protect future fertility. [11] * * * * * † * 6 Alla V.Boychuk 2020 [12] * * * * * * * 7 Azadeh Yousefnezhad 2018 [13] * * * * * * * 7 E.Demirdag 2016 [14] * * * * * * * 7 Gabriel Levin 2022 [15] * * * * * * * 7 G Dias Pereira 1999 [16] * * * ‡ * * * 8 Herve' Fernandez 2013 [17] * * * ‡ * * * 8 J.Bouyer 2000 [18] * * * * * * * 7 Jan I. Olofsson 2001 [19] * * * * * * * 7 Lars Bo Krag [20] * * * ‡ * * * 8 M.T. El-Sherbiny 2003 [21] * * * ‡ * † * 7 Marianne de Bennetot 2012 [22] * * * * * * * 7 N.Dalkalitsis 2006 [23] * * * * * * * 7 Senem Arda düz 2021 [24] * * * * * * * 7 Silvia Baggio 2021 [25] * * * * * * * 7 Volkan Turan 2011 [26] * * * * * * * 7 Wassan R. Alkhafajy 2018 [27] * * * * * † * 6 Yu-ting Shen2022 [28] * * * * * * * 7 Zahra Asgari 2021 [29] * * * * * * * 7…”
Section: Comparison Of Reproductive Outcomes After Mtx or Surgerymentioning
confidence: 99%
“…This study found that fertility was significantly higher after MTX than after surgical treatment (OR = 1.52; 95% CI: 1.20 to 1.92), with similar adverse pregnancy rates (OR = 0.89; 95% CI: 0.47 to 1.69). The surgery in this study included salpingostomy and salpingectomy, the surgical level varied in different places, and the reproductive outcomes after surgery were related to surgical precision, proficiency, [11] Greece RT --13 patients 23 patients MTX or surgery2 1 8/13 12/23 1/13 1/23 Alla V. Boychuk 2020 [12] Ukraine [17] France [18] France [24] Turkey PT [29] Iran RT 31.9 ± 5.6 64 patients MTX or surgery (1or2) and skills. The forest map in this study suggested slight heterogeneity and the funnel plot indicated no obvious publication offset.…”
Section: Comparison Of Reproductive Outcomes After Mtx or Surgerymentioning
confidence: 99%
“…These associations were not associated with length of pregnancy, suggesting that they are associated with fetal growth retardation rather than preterm birth. Traditionally, the causes of fetal development delay are divided into fetal, placental, and maternal [7,8,9]. Although fetal size is a physical parameter that can be measured at any stage of pregnancy, growth is a dynamic process that can only be assessed by repeated measurements.…”
Section: Introductionmentioning
confidence: 99%